DEVELOPMENT OF PROBLEM BASED LEARNING BASED STUDENT WORKSHEET ON DESCRIPTIVE TEXT MATERIAL FOR JUNIOR HIGH SCHOOL STUDENTS - Ilmanun, Lulu; Devianty, Rina (Universitas Muhammadiyah Makassar, 2025)
This research is motivated by the low descriptive text writing skills of seventh-grade junior high school students, which is caused by the use of conventional teaching methods and the lack of innovative learning media. This research aims to develop PBL-based LKPD on descriptive text material for seventh-grade students. The method used is research and development using the ADDIE model (analysis, design, development, implementation, and evaluation). The research subjects were 25 students from class VII A at SMP Swasta IRA. The data collection techniques are observation, interviews, questionnaires, and tests. Data were analyzed qualitatively and quantitatively through expert validation, questionnaires, and N-gain tests. The research results indicate that the developed LKPD was deemed very feasible by material experts at 92%, media experts at 90%, and language experts at 97%. The practicality level of the LKPD also received very practical results, with teacher responses at 92% and student responses at 83.68%. Additionally, the effectiveness testing results showed an improvement in students' writing skills, with an average N-gain of 0.56 in the moderate category. This research shows that PBL-based LKPD can be an alternative teaching material that supports a more active and creative learning process. This research also contributes to the development of teaching media in language education, as well as opening opportunities for further research in the development of other interactive teaching materials on different subjects or levels.